Style & statistics : the art of retail analytics - Bullard, Brittany (Hoboken : Wiley, 2016)
"The power of retail analytics is important but being able to interpret it in a way that the end business user or average shopper who wants to learn more can actually interpret and understand can be a challenge. The book will include information on current industry trends as well as why analytics have become so important in the industry. This book focuses on applications of analytics within merchandise assortment management, pricing, marketing, and customer intelligence. Each chapter will include how analytics can help retailers solve business issues. The book will also include interviews from different retailers. The end of the book will emphasize the personal value of utilizing analytics. It will talk about how utilizing analytics can help individuals' own careers by increasing efficiencies and accuracies. Information on how to expand their current knowledge will be included as well"--
Includes bibliographical references and index.
Machine generated contents note: Introduction Chapter 1: Changing Face of Retail Chapter 2: Merchandise Financial Planning Statistical Forecasting Chapter 3: Assortment Management Understanding Your Customer Understanding Product Choice Counts Understanding Current Product Performance Predicting the Evolution of Trends How much to buy? What sizes do I need? Chapter 4: Fulfillment Allocation Order Fulfillment Chapter 5: Pricing Pricing Analytics Regular Price Promotional Pricing Markdown/Clearance Pricing Pricing Maturity & Organizational Structures Chapter 6: Marketing Data Marketing Campaign Lift Analysis Customer Lifetime Value Customer Segmentation The Internet of Things Path to Purchase Chapter 7: In-Store Experience Store Labor Forecasting Assortment Optimization The Internet of Things Chapter 8: Cyber-Security EMV/Chip Cards Chargebacks Data Governance Chapter 9: Customer Journey Chapter 10: How to Gain Personal Value from Analytics The Citizen Data Scientist Change Agent Finding the Right Fit Chapter 11: How to Gain Personal Value from Analytics The Citizen Data Scientist Change Agent Finding the Right Fit Additional Resources Glossary Retail Math References Index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Retail trade -- Management; Retail trade -- Statistical methods; x; BUSINESS & ECONOMICS -- Industries -- Retailing; Retail trade -- Management; Retail trade -- Statistical methods